The Influence of Digital Marketing and Social Media on Product Creativity and Empowerment of Women's Culinary Group of Bojong Kulur Village, Bogor - setiawan, elfa; Junaidi, Ahmad; Rahman, Dinda Aulia (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study investigated the impact of digital marketing and social media on the creativity of products and the empowerment of culinary groups of women in Bojong Kulur village, Bogor. It also aimed to identify the most important factor in increasing product creativity and culinary group empowerment. A total of 180 respondents were purposefully selected from April to August 2023. Purposive sampling was used to collect questionnaires from producers and consumers. Descriptive statistical analysis using SPSS version 22 was used to analyze the data.The research results showed that digital marketing and social media have a significant impact on creativity empowerment. The study found that the significance value (Sig) of digital marketing strategy (X1) on creativity empowerment (Y) is 0.000, which is less than the significance level of 0.05. This means that there is a statistically significant relationship between digital marketing strategy and creativity empowerment. The study also found that the significance value (Sig) of the effectiveness of using social media (X2) on creativity empowerment (Y) is 0.001, which is also less than the significance level of 0.05. This means that there is a statistically significant relationship between the effectiveness of using social media and creativity empowerment. Based on these findings, the study concluded that digital marketing and social media have a simultaneous effect on creativity empowerment. This means that both digital marketing and social media can independently and jointly influence creativity empowerment.